Vyākaraṇa Mahābhāṣya of Patañjali on Pāṇini 3. 1 (Āhnikas 1 to 6) : text, translation with introduction, and technical notes - Patañjali; Thompson, Stephen Peter (Delhi : Motilal Banarsidass Publishers, 2010)
Exegesis with the text of Pāṇini's Aṣṭādhyāyī, a classical Sanskrit grammatical treatise.
pt. 1. General introduction -- pt. 2. Text and translation -- pt. 3. Appendix.
Bibliografija: str. [xi]-xiii i kazalo.
Na engleskom i sanskrtu.
Keywords: sanskrt -- gramatika; Pāṇini -- Aṣṭādhyāyī